2012
DOI: 10.1073/pnas.1212294109
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of gastric H + ,K + -ATPase with a single occupied cation-binding site

Abstract: Gastric H + ,K + -ATPase is responsible for gastric acid secretion. ATPdriven H + uptake into the stomach is efficiently accomplished by the exchange of an equal amount of K + , resulting in a luminal pH close to 1. Because of the limited free energy available for ATP hydrolysis, the stoichiometry of transported cations is thought to vary from 2H + /2K + to 1H + /1K + per hydrolysis of one ATP molecule as the luminal pH decreases, although direct evidence for this hypothesis has remained elusive. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…A low-resolution crystal structure of the H + ,K + -ATPase obtained at acidic pH in the presence of the K + congener Rb + shows that one bound Rb + ion occupies a site equivalent to site II of the Na + ,K + -ATPase, whereas the occupancy of site I is very low (8).…”
mentioning
confidence: 99%
“…A low-resolution crystal structure of the H + ,K + -ATPase obtained at acidic pH in the presence of the K + congener Rb + shows that one bound Rb + ion occupies a site equivalent to site II of the Na + ,K + -ATPase, whereas the occupancy of site I is very low (8).…”
mentioning
confidence: 99%
“…ATPase Assay-The ATPase activity of P4-ATPase was determined as described (27)(28)(29)(30)(31) with slight modifications. In brief, the purified protein (10 ng) was preincubated for 10 min at room temperature in 40 l of the reaction mixture (40 mM MES/Tris buffer (pH 7.0), 150 mM NaCl, 5% glycerol, 5 mM MgCl 2 , 7 mM DTT, 600 M ATP, and 0.05% LMNG) and incubated for 20 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that Na + /K + -ATPase and SERCA sequence structures are 30 % identical and 65 % similar [2], this is the reason why SERCA model was used for Na + /K + -ATPase studies until it was crystalized. Also, both proteins have an α subunit, with 10 transmembrane spans, but Na + /K + -ATPase differs in having also β and γ isoforms, with 12 transmembrane spans, so two subunits should affect the α subunit conformation of Na + /K + -ATPase [3,4]. In this review, we concentrate only in P2C-ATPases: H + /K + -ATPases and Na + /K + -ATPase.…”
Section: Introductionmentioning
confidence: 98%